Force Majeure Clause in Employment Contracts: Its Relevance in Malaysian Industrial Jurisprudence - Ali Mohamed, Ashgar Ali; Ramalingam, Chithra Latha; Ahmad, Muhamad Hassan (LexisNexis Malaysia Sdn Bhd, 2020)
If a pandemic such as Covid-19 is once again contemplated, the future contract of employment may be leading to the recognition of the force majeure clause. Current legal scenario to include the force majeure clause in contract of employment must examine the recognition and applicability of the clause by the legislature. Can an obligation be imposed on the both parties be just and equitable in that the party relying on the clause will have to give reasonable notice to the other party in event the contract becomes impossible to perform and what would be the compensation allowable to the other party?